New Arbitration Act: Collaboration and judicial control - Castillo Freyre, Mario (2008)
Although the principle of autonomy of the arbitration is clear, it does not imply necessarily that the judicial courts must ignore the arbitration. In this article, the judicial attendance in the action of the tests in arbitration is treated, and because of the lack of the «imperium» of the arbitrators the production of certain means of test are difficult. Finally, it deals with judicial assistance in the execution of a precautionary measure and in the execution of the award. On this last subject it is indicated that although the award finds its origin in the will of the parts, it is not less certain that often it must be gone to forced execution.